An electrothermal instability: the influence of albedo boundary conditions on the stationary states of an exactly solvable model - Schat, Carlos; Wio, Horacio S. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Schat, Carlos Comisión Nacional de Energía Atómica; Argentina